The left and the lucky : a novel [compact disc, unabridged] - Vlautin, Willy (HarperCollins, 2026)
Eddie Wilkens is a workaholic house painter in his early forties. Next door, a woman and her two sons move in. The younger boy, eight-year-old Russell, lives in constant terror of his increasingly lost and troubled fifteen-year-old brother Curtis. When Russell begins waiting in Eddie's backyard for him to get off work, Eddie offers the boy small acts of kindness and a glimpse into a world of hope and humor. In return, Russell gives Eddie a reason to carry on and helps him lay to rest the guilt that has plagued him for half of his life. Together, this makeshift father and son begin to build better life, daring to trade the bleakness and cynicism around them for hope and friendship.